Customary Law in Subject Field of Ethnological Examinations - A. N. Sadovoy (Научный диалог)
The article raises the question of the inclusion customary law in the subject field of ethnological examinations as a separate section devoted to functioning in the environment of the studied ethnic groups. The relevance of the development is the manifestation of this phenomenon as a sustained stabilization factor (regulator) of ethno-social situation in a number of subjects of the Russian Federation. In addition, there is an ambivalent attitude to this phenomenon by regional authorities. Based on the experience of the ethnological expertise formalization of primary data obtained during field work is proposed on the five key features, defining the place of customary law in current legal systems. The author focuses on the need for analysis of the interaction of two ethno-social processes: the conservation (formation) of social institutions which function is the regulation of social relations based on customary law and development of a wide range of forms of ethnic entrepreneurship. It is proved that the change in the subject area should be based on correction of research procedures and a list of key indicators in the model regulations for ethnological assessments.